Gelatin/nano‐hydroxyapatite hydrogel scaffold prepared by sol‐gel technology as filler to repair bone defects. Issue 7 (17th April 2018) - Raucci, Maria Grazia; Demitri, Christian; Soriente, Alessandra; Fasolino, Ines; Sannino, Alessandro; Ambrosio, Luigi
Abstract: This study reports on the development of a scaffold with a gradient of bioactive solid signal embedded in the biodegradable polymer matrix by combining a sol–gel approach and freeze‐drying technology. The chemical approach based on the sol–gel transition of calcium phosphates ensures the particles dispersion into the gelatin matrix and a direct control of interaction among COOHgelatin /Ca 2+ ions. Morphological analysis demonstrated that on the basis of the amount of inorganic component and by using specific process conditions, it is possible to control the spatial distribution of nanoparticles around the gelatin helix. In fact, methodology and formulations were able to discriminate between the different hydroxyapatite concentrations and their respective morphology. The good biological response represented by good cell attachment, proliferation and increased levels of alkaline phosphatase as an indicator of osteoblastic differentiation of human mesenchymal stem cells toward the osteogenic lineage, demonstrating the effect of bioactive solid signals on cellular behavior. Furthermore, the inhibition of reactive oxygen species production by composite materials predicted potential anti‐inflammatory properties of scaffolds thus confirming their biocompatibility. Indeed, these interesting biological results suggest good potential application of this scaffold as filler to repair bone defects. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 2007–2019, 2018.